World Bank Lending and Financial Sector Development - Cull, Robert J. 1994- (The World Bank, 2005)
Using a new database of World Bank loans to support financial sector development, the authors investigate whether countries that received such loans experienced more rapid growth on standard indicators of financial development than countries that did not. They account for self-selection with treatment effects regressions, and also use propensity score matching techniques. The authors ' results indicate that borrowing countries had significantly more rapid growth in M2/GDP than non-borrowers, and swifter reductions in interest rate spreads and cash holdings (as a share of M2). Borrowers also had higher private credit growth rates than non-borrowers in treatment effects regressions, but not in standard panel regressions with fixed country effects. On the whole, however, the results indicate significant advantages for borrowers over non-borrowers in terms of financial development